Analisis Pemasaran untuk Peningkatan Penjualan Madu dengan Metode Analisis Five Forces - Sufrotun Khasanah; Jamal; Alfan Mubarok (Fakultas Teknik dan Rekayasa, 2022)
The honey bee, which is popular in the community, is known to have a sting that is quite discouraging. However, there are stingless bees that can also produce honey. Apart from being stingless, the stingless bee species that are starting to bloom in Indonesia are no less efficacious. The purpose of this study is to find out what problems occur in marketing and to provide an analysis of competitive strategies that should be carried out. The method used in this study is the five force method. The results of this study state that the conditions of competition faced in the honey industry are very tight. This is shown from the analysis of the five forces. Where the five forces analysis shows that there are influential threats to the honey industry, namely the threat of new entrants, the threat of consumer power and the threat of competition among industries. Apart from threats, there are opportunities that stores can take advantage of to increase sales, namely sales opportunities in modern markets, sales opportunities on social media and opportunities for collaboration with herbal medicine sellers. Strategies that can be applied to increase sales and profits are: cooperation strategies with herbal medicine sellers, marketing strategies through social media, sales strategies in modern markets. Keywords : Strategy, Strength, Marketing